Tradisi Keagamaan dan Proses Sosial pada Kaum Muslim Pedesaan - Agus Riyadi (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2018)
Religious ceremonies that are usually carried out by Javanese are inherited from the ancestors. There are two types of religious ceremonies in the form of salvation in Javanese society, namely life cycle salvation ceremonies and Islamic religious holidays. The research aims to find an understanding of the traditions of religious ceremonies and social processes for Muslims in Karangrayung District, Grobogan Regency. Data collection methods were obtained through observation, interviews, documentation and literature study. After that, the data is analyzed qualitatively-descriptive-interpretative. The results showed that there were seven religious ceremonies and social processes which until now were still commemorated by the Karangrayung people, namely: Sura (Muharam), Rajaban selametan, Mauludan selametan, Selametan Ruwahan, Selametan Likuran, Selametan Bodonan, and Selametan Besar which were held on the 10th Zulhijjah. The perception of the people of Karangrayung on religious ceremonies and social processes is a form of virtue that is recommended by Islamic teachings that contain values: 1) charity, 2) ukhwah Islamiyah, 3) help, and 4) share with others